Laparoscopic-assisted repair of inguinal undescended testis with concurrent incarcerated hernia in children: a single-center experience - You, Jia; Sun, Jie; Jing, Shen; Liu, Xin; Wang, Jun (Frontiers in Pediatrics, 2025)
PurposesWe report clinical, operative, and outcome data for laparoscopic- assisted minimal procedure for treating unilateral inguinal undescended testis (UDT) with concurrent ipsilateral incarcerated hernia in children.MethodsEarly-stage cases were defined as those presenting within 24 h of symptom onset with stable vital signs and absence of peritonitis, intestinal necrosis, or testicular necrosis. A retrospective analysis was conducted on patients undergoing laparoscopic-assisted hernia repair and trans-scrotal orchidopexy (LAHRTO) procedure.ResultsA total of 14 cases were enrolled (Left, n = 4; Right, n = 10). Incarcerated hernia contents comprised viable omentum or bowel, without necrosis or intestinal perforation. Ten cases achieved successful laparoscopic reduction, while four cases required conversion to open inguinal incision due to failed reduction. All the testes were preserved and underwent the LAHRTO procedure except for those that converted. Notably, five cases of contralateral patent processus vaginalis (PPV) were identified, allowing for synchronous closure during surgery. The average operation time was (46.8 ± 5.2) min, resulting in a success rate of 71.4% (10/14). At 16–24 months of follow-up, two testes showed partial atrophy. No wound infections, hernia recurrences, or testicular retractions were observed.ConclusionsOur initial findings suggest that the LAHRTO procedure appears safe and feasible for early-stage inguinal UDT with concurrent incarcerated hernia in children, reducing inguinal incisions and enabling concurrent contralateral PPV management. A larger number of cases with longer follow-up is needed to validate the results of the current study in an evidence-based manner.